Struktur Modal Dan Kinerja Keuangan Perusahaan Manufaktur - Erawati, Teguh; De Kasi, Angelia Alfanny (Universitas Muhammadiyah Metro, 2024)
This study aims to prove the effect of good corporate governance and capital structure on the company's financial performance. The sampling technique used purposive sampling method. The population in this study were 183 companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 with a total sample of 71 companies that met the criteria. The method of analysis uses the SPSS version 26 statistical application for windows. The results of this study indicate that good corporate governance has an effect on financial performance and capital structure has no effect on financial performance